Psychological Well-Being In Family Caregivers Of Stroke Patients - Prima, Ashar; Iriani, Rida Dwika; Andas, Amzal Mortin (Nursing Genius Journal, 2024)
Background – Stroke remains a major health concern in Indonesia, with rising morbidity and mortality rates annually. The psychological well-being of caregivers is crucial to ensure optimal care for their family members. Objective – This study aims to examine the psychological well-being of family caregivers of stroke patients. Methods – A quantitative descriptive approach was employed, with non-probability sampling. The study population consisted of 100 family caregivers of stroke patients from two regions (Bogor and Bekasi). Data were collected using the Ryff’s Scale of Psychological Well-Being (RPWB) questionnaire, comprising 18 statements representing six dimensions of psychological well-being. Results – The findings revealed that 68% of caregivers exhibited high psychological well-being, with an average score above 96.18. The dimensions were ranked from lowest to highest: purpose in life (48%), environmental mastery (54%), autonomy (58%), self-acceptance (68%), personal growth (68%), and positive relations with others (73%). The most dominant dimension was positive relations (73%), followed by self-acceptance and personal growth. Conclusion – Family caregivers of stroke patients generally demonstrate high psychological well-being.